POLARISASI MASYARAKAT ARAB-HADHRAMI DI SURAKARTA, 1914-1950 - Taslim Batubara; Muhammad Wildan (Jurnal Sosiologi Agama)
This article aims to analyze the phenomenon of polarization that is occurred among the Arab-Hadrami community in Surakarta during the period 1914-1950 and the influencing factors. The research examines the polarization of the Arab-Hadrami community in Surakarta using a sociological approach. The concepts utilized in this study are polarization, conflict, and social integration. The researchers employs the Social Polarization theory to observe sharp differences between social groups within the society, leading to their isolation and conflicts. The research follows a historical research method with four stages: source collection, criticism, interpretation, and historiography. Two types of data sources are utilized: primary and secondary sources. The findings reveal that the polarization among the Arab-Hadrami community in Surakarta from 1914 to 1950 occurred due to three factors: the Fatwa Solo, the differences in perspectives on titles and traditions, and orientation toward the homeland. The forms of polarization within the Arab-Hadrami community in Surakarta between 1914-1950 emerged through social organizations, education, and newspapers. Other results related to the impact of polarization among the Arab-Hadrami community in Surakarta from 1914-1950 manifest in two aspects: the search for unity organizations among the Arab-Hadrami community in Surakarta and the integration of the Arab-Hadrami community in Surakarta into Indonesia